Islam dan Perilaku Politik di Timur Tengah - Darmawan, Arief Bakhtiar (Laboratorium Hubungan Internasional, FISIP, Universitas Jenderal Soedirman, 2018)
This paper aims to analyze religionâs roles related to the political activities in the contemporary Middle East. Constructivism is a framework that offers the way to understand the phenomenon. Constructivism provides a place for the influence of non-material factors such as the value, identity, and purpose of actor behavior in politics. This study used descriptive-interpretative method to acknowledge the problem formulation. Through the lenght of descriptive-interpretative method, author carried out data management, unification, and examination by exertly looking for patterns and relations regarding the role of Islam in political activities in Middle-East. In this article, the author examines through two levels of analysis, ie state level and regional level. At the state level, Islamic political ideology grows in a modern state and often confronts democracy. The debate over the application of Islamic law, the involvement in elections, and the adaptation of Islamic justice principles and the principle of equality are the discourses that characterize political activity in the Middle East. At the regional level, Islam exerts impact in foreign policy in the region. The regional tensions between Sunni and Shiite groups, the resistance in the context of jihad, and the emergence of ISIS are part of the conflict that contributes to regional instability. These political behaviors shows that Islam is not a religion with a single interpretation. Keywords: Islam, Middle East, constructivism, modern states, foreign policy Artikel ini bertujuan untuk menganalisis peran atau pengaruh Islam dalam aktivitas politik di kawasan Timur Tengah terkini. Konstruktivisme merupakan kerangka pemikiran yang menyediakan jalan untuk memahami fenomena tersebut. Konstruktivisme memberi tempat bagi pengaruh faktor-faktor non-material seperti nilai, identitas, dan maksud dari perilaku aktor dalam dunia politik. Penelitian ini menggunakan pendekatan deskriptif-interpretatif untuk menjawab rumusan masalah. Melalui pendekatan deskriptif-interpretatif, penulis melakukan pengaturan, penyatuan, dan pemeriksaan data dengan berupaya mencari pola dan relasi mengenai peran atau pengaruh Islam dalam aktivitas politik di Timur Tengah. Dalam artikel ini, penulis meneliti melalui dua level analisis, yaitu level negara dan level regional. Dalam level negara, ideologi politik Islam tumbuh dalam negara modern dan seringkali berhadapan dengan demokrasi. Perdebatan mengenai penerapan syariat Islam, keterlibatan dalam pemilihan umum, serta penyesuaian prinsip keadilan Islam dan prinsip persamaan hak merupakan diskursus yang mewarnai aktivitas politik di Timur Tengah. Dalam level regional, Islam memberi pengaruh dalam politik luar negeri di kawasan. Ketegangan regional antara kelompok Sunni dan Syiah, perlawanan dalam konteks jihad, serta kemunculan ISIS adalah bagian dari konflik yang menyumbang ketidakstabilan kawasan. Perilaku-perilaku politik tersebut menunjukkan bahwa Islam bukan agama dengan makna yang tunggal. Kata kunci: Islam, Timur Tengah, konstruktivisme, negara modern, politik luar negeri